2019
DOI: 10.1002/chir.23050
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric separation of prothioconazole and prothioconazole‐desthio on chiral stationary phases

Abstract: Prothioconazole is a type of broad-spectrum triazole thione fungicide developed by the Bayer Company. Prothioconazole-desthio is the main metabolite of prothioconazole in the environment. In our study, enantiomeric separation of prothioconazole and prothioconazole-desthio was performed on various chiral stationary phases (CSPs) by high-performance liquid chromatography (HPLC). It was found that polysaccharide CSPs showed better ability than brushing CSPs in enantiomeric separation. The successful chiral separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A method for the separation of α-tocopherol enantiomers was successfully developed with a Lux Cellulose-1 column [ 57 ]. Several polysaccharide-based CSPs were tested for enantiomeric separation of the antifungal agent prothioconazole and its metabolite prothioconazole-desthio, and the Lux Cellulose-1 column was rated as the best [ 58 ]. A comparative study was performed with chiral basic drugs on amylose- and cellulose phenylcarbamate-based chiral columns with a focus on substituent electron-donor and electron-acceptor effects.…”
Section: Polysaccharide-based Stationary Phasesmentioning
confidence: 99%
“…A method for the separation of α-tocopherol enantiomers was successfully developed with a Lux Cellulose-1 column [ 57 ]. Several polysaccharide-based CSPs were tested for enantiomeric separation of the antifungal agent prothioconazole and its metabolite prothioconazole-desthio, and the Lux Cellulose-1 column was rated as the best [ 58 ]. A comparative study was performed with chiral basic drugs on amylose- and cellulose phenylcarbamate-based chiral columns with a focus on substituent electron-donor and electron-acceptor effects.…”
Section: Polysaccharide-based Stationary Phasesmentioning
confidence: 99%
“…Previous research has shown that prothioconazole inhibits the 14α-demethylation of lanolin, which is the precursor of sterol biosynthesis in fungi, and therefore should be considered a member of the sterol 14α-demethylation inhibitor (DMI) group of fungicides [ 6 8 ]. In addition to its broad-spectrum activity, prothioconazole has many other desirable characteristics including good internal absorption, long duration of activity, and low environmental impact [ 9 ]. The Fungicide Resistance Action Committee (FRAC) classifies DMI fungicides in the G1 subgroup of Sterol Biosynthesis Inhibitors (SBI) that are recommended for general use in all crops [ 10 ], and prothioconazole is widely used for the prevention and control of disease in field crops such as wheat, soybean, and rice [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its broad-spectrum activity, prothioconazole has many other desirable characteristics including good internal absorption, long duration of activity, and low environmental impact [ 9 ]. The Fungicide Resistance Action Committee (FRAC) classifies DMI fungicides in the G1 subgroup of Sterol Biosynthesis Inhibitors (SBI) that are recommended for general use in all crops [ 10 ], and prothioconazole is widely used for the prevention and control of disease in field crops such as wheat, soybean, and rice [ 6 , 9 ]. Indeed, studies have shown that prothioconazole provides excellent control of almost all fungal diseases, with especially high activity against wheat scab, dry blight, and powdery mildew [ 6 ], and that when applied at a rate of 200 g/hm 2 it provided equal to or better control than other commonly used fungicides such as epoxiconazole, tebuconazole and cyprodinil [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC has been commonly applied to the separation and analysis of drug enantiomers because of its more prominent advantages of fast separation, high efficiency, good reproducibility, and easy operation [5][6][7][8][9] than other chiral separation methods such as CE [10] and supercritical fluid chromatography (SFC) [11][12][13]. To date, different chiral stationary phases (CSPs) have been developed to achieve the enantioseparation of various chiral drugs.…”
Section: Introductionmentioning
confidence: 99%